2019
DOI: 10.1016/j.heliyon.2019.e03051
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of radiocesium in animals, plants and fungi in Svalbard after the Fukushima Daiichi nuclear power plant disaster

Abstract: An earthquake struck the eastern part of Japan on March 11, 2011. The Fukushima Daiichi nuclear power plant was severely damaged by the earthquake and subsequent tsunami, leading to the emission of large amounts of radioactive pollutants, including 134 Cs and 137 Cs, into the environment. From August 23 to September 1 in 2011, and from August 27 to September 4 in 2013, we collected samples of animals, plants, fungi and lichens from Svalbard, Norway and measured the radioactivity of 134 Cs and 137 Cs contained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The authors also point to the serious problem of radionuclide bioaccumulation. However, a recent study by Mezaki et al (2019) on 134 Cs and 137 Cs in animals and plants showed a lack of radioactivity in most of the samples tested. The low activity of 137 Cs was demonstrated for some lichens and mushrooms.…”
Section: Heavy Metalsmentioning
confidence: 85%
“…The authors also point to the serious problem of radionuclide bioaccumulation. However, a recent study by Mezaki et al (2019) on 134 Cs and 137 Cs in animals and plants showed a lack of radioactivity in most of the samples tested. The low activity of 137 Cs was demonstrated for some lichens and mushrooms.…”
Section: Heavy Metalsmentioning
confidence: 85%